JNK activity in somatic stem cells causes loss of tissue homeostasis in the aging Drosophila gut. - Biteau, B.; Hochmuth, C.E.; Jasper, H. (Cell Stem Cell, 2008)
Metazoans employ cytoprotective and regenerative strategies to maintain tissue homeostasis. Understanding the coordination of these strategies is critical to developing accurate models for aging and associated diseases. Here we show that cytoprotective Jun N-terminal kinase (JNK) signaling influences regeneration in the Drosophila gut by directing proliferation of intestinal stem cells (ISCs). Interestingly, this function of JNK contributes to the loss of tissue homeostasis in old and stressed intestines by promoting the accumulation of misdifferentiated ISC daughter cells. Ectopic Delta/Notch signaling in these cells causes their abnormal differentiation but also limits JNK-induced proliferation. Protective JNK signaling and control of cell proliferation and differentiation by Delta/Notch signaling thus have to be carefully balanced to ensure tissue homeostasis. Our findings suggest that this balance is lost in old animals, increasing the potential for neoplastic transformation.